Characterization of fecal microbiota in cervical cancer patients associated with tumor stage and prognosis - Chang, Lei; Qiu, Luojie; Lei, Ningjing; Zhou, Junying; Guo, Ruixia; Gao, Feng; Dong, Shiliang; Chen, Mengyu; Wu, Fengling; Qin, Bo (Frontiers in Cellular and Infection Microbiology, 2023)
Cervical cancer (CC) is the fourth most frequent malignancy among women worldwide, and its prevention and treatment are evolving rapidly. The gut microbiota has been reported to play a crucial role both in the preservation of homeostasis and the development of cervical cancer. In this study, we collected fecal samples to investigate the microbial signatures in cervical cancer patients compared with healthy controls using 16S rRNA sequencing analysis and metagenomic next-generation sequencing (mNGS) testing. Our findings demonstrated a substantial difference in the gut microbiota composition of cervical cancer patients and healthy controls. The disease and stage were most significantly negatively correlated with Ruminococcus 2, which might be considered a potential clinically relevant biomarker. Functions of differential microbiomes were also analyzed, indicating significant differences in metabolisms and biosynthesis between the two groups. These findings demonstrate that patients with cervical cancer have certain species of gut microbiota that are exclusive to them and particular species have the potential to be used in the prognosis of cervical cancer.